Edukasi Literasi Obat Berbasis Interaktif untuk Meningkatkan Pengetahuan Masyarakat di Pulau Sumbawa - Ika Wahyuni; Gilang Pratama Putra; Lalu Sanik Wahyu Fadil Amrulloh; M Ari Wisnu; Jamiluddin Jamiluddin (Prima Abdika: Jurnal Pengabdian Masyarakat, 2026)
Low levels of medication literacy among communities and adolescents may lead to medication misuse, irrational self-medication, increased risk of adverse effects, and antibiotic resistance. Medication literacy encompasses the ability to access, understand, evaluate, and appropriately use medication-related information. This community service program aimed to improve medication literacy through interactive educational interventions in Sumbawa Island. The program employed interactive lectures, group discussions, medication-use simulations, and the distribution of educational materials. Activities were conducted in public areas and involved 50 respondents, consisting of adolescents and members of the general public. A pre-test and post-test design was used to evaluate improvements in participants’ ability to access, understand, evaluate, and use medication information. The results demonstrated significant improvements across all measured variables. Correct knowledge regarding appropriate sources of side-effect information (health professionals) increased from 30% to 100%. The ability to read and interpret medication dosage labels improved from 46% to 84%. Awareness of the need to complete prescribed antibiotics rose from 6% to 96%. Critical attitudes toward medication advertisements on social media also improved, with 82% of respondents indicating the need to verify information sources after the intervention. Practical skills in medication use increased substantially, including correct understanding of dosing intervals (from 2% to 78%) and appropriate emergency action by taking poisoning victims to healthcare facilities (from 40% to 100%). In conclusion, interactive medication literacy education effectively enhances knowledge, attitudes, and skills related to safe and rational medication use among communities and adolescents. This program is feasible for replication as part of broader public health strategies to strengthen health literacy.